2001
DOI: 10.12968/ijpn.2001.7.12.9283
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Western Australian Indian families: concerns and coping strategies

Abstract: Discussion with families of Indian clients with cancer living in Western Australia and their anecdotal reports of stress related to care lead to the development of this descriptive, qualitative study. In particular, the study addresses the concerns of Western Australian families of Indian clients with cancer and the coping strategies they employed. Six family members participated in face-to-face interviews. Content analysis revealed a four-phase process that family members described in response to the cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The degree of influence culture has on family members' ability to adapt to caring for a loved one with cancer is very difficult to determine. However, the cultural beliefs of some people may hinder their willingness to actively seek professional help and resultant support services (Sellappah et al, 2001). Weinland (2009) found that most African American men acting as caregivers refused the entry of formal support services into their homes because of financial or privacy concerns.…”
Section: Cultural Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…The degree of influence culture has on family members' ability to adapt to caring for a loved one with cancer is very difficult to determine. However, the cultural beliefs of some people may hinder their willingness to actively seek professional help and resultant support services (Sellappah et al, 2001). Weinland (2009) found that most African American men acting as caregivers refused the entry of formal support services into their homes because of financial or privacy concerns.…”
Section: Cultural Backgroundmentioning
confidence: 99%
“…Similarly, Costantini, Beccaro, Merlo, and the ISDOC Study Group (2005) concluded that the primary support person of patients of Italian descent was predominantly a child or spouse, with very few caregivers or patients accepting or seeking any kind of support outside the family. In a small study by Sellappah et al (2001), six Western Australian Indian families indicated that the provision of cancer care in the home environment allowed cultural rituals to be maintained with ease within the family when compared to a hospital setting.…”
Section: Cultural Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] The literature shows that little is known about Indian family member's experiences of being caregivers, as well as their expectations of the palliative care services. [6]…”
Section: Introductionmentioning
confidence: 99%